2004
DOI: 10.1063/1.1840127
|View full text |Cite
|
Sign up to set email alerts
|

Ce 3 + -doped fibers for remote radiation dosimetry

Abstract: A radioluminescent (RL) dosimetric system, based on a SiO2 optical fiber with the core doped by Ce3+ ions as luminescent activators has been investigated. Structural and optical properties of the luminescent fiber have been studied by Raman, refractive index, RL and scintillation time decay measurements, and compared to those obtained on bulk material. The RL response of a composite fiber made of a short portion of active Ce-doped fiber coupled to a long commercial one has been investigated by x-ray irradiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
71
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(80 citation statements)
references
References 16 publications
9
71
0
Order By: Relevance
“…This feature can be ascribed to a readjustment of the silica matrix due to the heating process required by the fiber drawing, which influences the traps distribution and consequently the trap-related phenomena like RL hysteresis, persistent luminescence, and TSL. In this respect, we recall that previous Raman measurements performed in bulk sol-gel silica and fibers revealed that the intensities of D1 and D2 peaks due to symmetric stretching modes of fourfold and threefold rings of SiO2 tetrahedra are higher in the fiber with respect to the bulk [34]. This is also in accordance with what observed on silica samples subjected to thermal treatments at different temperatures, where the formation of fourfold and threefold rings of SiO2 tetrahedra increased exponentially by temperature increasing [35].…”
Section: Rl Hysteresis and Tsl Glow Curvesmentioning
confidence: 98%
“…This feature can be ascribed to a readjustment of the silica matrix due to the heating process required by the fiber drawing, which influences the traps distribution and consequently the trap-related phenomena like RL hysteresis, persistent luminescence, and TSL. In this respect, we recall that previous Raman measurements performed in bulk sol-gel silica and fibers revealed that the intensities of D1 and D2 peaks due to symmetric stretching modes of fourfold and threefold rings of SiO2 tetrahedra are higher in the fiber with respect to the bulk [34]. This is also in accordance with what observed on silica samples subjected to thermal treatments at different temperatures, where the formation of fourfold and threefold rings of SiO2 tetrahedra increased exponentially by temperature increasing [35].…”
Section: Rl Hysteresis and Tsl Glow Curvesmentioning
confidence: 98%
“…The RIA is affected by: 1. the manufacturing conditions, the parameters related to the technology used in producing the optical fiber: the deposition conditions, the draw process characteristicsdraw speed, fiber drawing tension, the preform deposition temperature, oxygen-toreagent ratio (02/R) used during core and clad deposition (Friebele, 1991;Girard et al, 2006;Hanafusa et al, 1986); 2. the existence, prior to the irradiation, of some precursors (Miniscalco et al, 1986); 3. the dopants present in the optical fiber core or cladding (pure silica, or doped with Ce, Er, Ge, F, N, P, Yb, high-OH, low-OH, high-Cl, low-Cl, H2-loading), (Arvidsson et al, 2009;Berghmans, 2006;Berghmans et al, 2008;Bisutti et al, 2007;Brichard & Fernandez Fernandez, 2005;Friebele, 1991;Girard et al, 2004a;Girard et al, 2004b;Girard et al, 2008;Griscom et al, 1996;Henschel et al, 1992;Kuyt et al, 2006;Lu et al, 1999;Mady et al, 2010;Paul et al, 2009;Regnier et al, 2007;Vedda et al, 2004;Wijnands et al, 2007), in some situations such ingredients contribute to the radiation hardening (Brichard et al, 2004;Brichard & Fernandez Fernandez, 2005;Girard et al, 2009); 4. the residual substances remaining after the manufacturing process, as for example chlorine having an associated color center in the UV spectral range, which can extend into the visible Girard & Marcandella, 2010); 5. the type of radiation to which the optical fiber is subjected (Arvidsson et al, 2009;Bisutti et al, 2007;Brichard et al, 2001;Calderón et al, 2006;Girard et al, 2004a;Girard et al, 2004b;…”
Section: Optical Fibers Performances Under Irradiationmentioning
confidence: 99%
“…The scintillator consisted in a small portion of Yb-doped silica optical fiber with diameter of approximately 200 µm and length 3 mm, prepared by sol-gel and "rod in tube" technique. Details of the synthesis procedure of doped-silica matrices are available elsewhere 28) . The doped portion was connected by fusion spicing with a 1 m long commercial optical fiber (Polymicro Technologies, AZ, USA).…”
Section: The Dosimetric Systemmentioning
confidence: 99%